Evaluating Diabetes Care for Patients With Serious Mental Illness Using the Chronic Care Model - Kelly Vaez; Lauren Diegel-Vacek; Catherine Ryan; Pamela Martyn-Nemeth (SAGE Publishing, 2017)
People with serious mental illness (SMI) have a higher incidence of type 2 diabetes mellitus (T2DM) and shorter life span due to medical health problems. The chronic care model (CCM) has been used to improve care of patients with T2DM. One clinical organization that provided primary care to patients with SMI had excellent diabetes outcomes but did not have information on how they achieved those outcomes. Thus, we conducted a pilot study chart review for 30 patients with T2DM and SMI to determine how well the clinic's system aligned with the overall CCM components and which components correlated with diabetes control. We also evaluated use of the CCM using the Assessment of Chronic Illness Care provider survey. Results showed that the clinic had an overall basic implementation level of the CCM, which allows opportunity for improvement. Two elements of the CCM were correlated with hemoglobin A 1C and both were in an unexpected direction: self-management support in the variable of percentage of visits that included patient-specific goal-setting ( r s = .52; P = .004) and delivery system design in the variable of number of nurse practitioner visits per study period ( r s = .43; P = .02). These findings suggest that the clinic may have made more concentrated efforts to manage diabetes for patients who were not in good diabetes control. Providers noted the influence of SMI and social service organization support on these patients' clinical outcomes. The findings will be reexamined after a fuller implementation of the CCM to further improve management in this population.